Improvement of the strength of poly(acrylic acid) hydrogels by the incorporation of functionally modified nanocrystalline Cellulose. Issue 6 (7th September 2020) - Hossain, Md. Amzad; Roy, Chanchal Kumar; Sarkar, Stephen Don; Roy, Hridoy; Howlader, A. Hasan; Firoz, Shakhawat H.
Abstract : Incorporation of dicarboxylate nanocrystalline cellulose (DCNC) and dialdehyde nanocrystalline cellulose (DANC) into poly(acrylic acid) (PAA) hydrogel remarkably improved the mechanical performance. Abstract : Finding different strategies to incorporate functionalized nanocrystalline cellulose (NCC) into polymeric materials is a fascinating domain of current research. In this study, dialdehyde nanocrystalline cellulose (DANC) and dicarboxylated nanocrystalline cellulose (DCNC) were prepared by the functionalization of NCC at the C-2 and C-3 positions of the glucose moiety by a selective chemical oxidation process. The functionalized NCCs were successfully incorporated into poly(acrylic acid) (PAA) hydrogels to improve their mechanical properties. The PAA hydrogel incorporated with DCNC (PAA-DCNC) showed the most significant enhancement in mechanical properties compared to the neat PAA, PAA-NCC, and PAA-DANC hydrogels. The Young's modulus of the neat PAA hydrogel was only 90.2 kPa, which was increased by about six times (619.1 kPa) by the addition of a minimal amount (0.058 wt%) of DCNC with 40% carboxylation (DCNC-40). Six times enhancement in the tensile strength was observed in the presence of DCNC-40. The toughness of PAA-DCNC-40 hydrogel was 522.2 kJ m −3, which was only 97.4 kJ m −3 in the absence of DCNC. Mechanical and water swelling properties of the prepared hydrogels were examined to understand the mechanism of interaction for the enhancement of performance.